2022
DOI: 10.1186/s13034-022-00469-8
|View full text |Cite
|
Sign up to set email alerts
|

School educational models and child mental health among K-12 students: a scoping review

Abstract: Background The promotion of mental health among children and adolescents is a public health imperative worldwide, and schools have been proposed as the primary and targeted settings for mental health promotion for students in grades K-12. This review sought to provide a comprehensive understanding of key factors involved in models of school education contributing to student mental health development, interrelationships among these factors and the cross-cultural differences across nations and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 221 publications
0
10
0
3
Order By: Relevance
“…Reporting health examination results can also be used as a communication tool between parents and teachers. Besides that, it can be used as promotive and preventive activity for children (Natalia & Anggraeni, 2022;Yu et al, 2022). Previous study state that through networking, student health mapping can be carried out, detecting student lifestyles that result in health problems, learning process problems and detecting wrong behavior related to health (Mulazimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reporting health examination results can also be used as a communication tool between parents and teachers. Besides that, it can be used as promotive and preventive activity for children (Natalia & Anggraeni, 2022;Yu et al, 2022). Previous study state that through networking, student health mapping can be carried out, detecting student lifestyles that result in health problems, learning process problems and detecting wrong behavior related to health (Mulazimah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…• Social-emotional learning interventions: the acquisition of cognitive and non-cognitive skills, sometimes referred to as "socio-emotional skills" or "general skills" conducive to healthy development (interpersonal skills, responsible decision-making, self-awareness, social awareness and self-control) [21][22][23][24]); • Mindfulness interventions: the capacity to "intentional self-regulation of attention from moment to moment, and other definitions have since emerged centering on focal In both ECEC settings and primary schools, the socialemotional learning interventions tend to focus on the regulation of emotions, problem-solving and coping skills, empathy, self-esteem, wellbeing, positive emotion, social capacities, building better relationships between teachers and pupils, satisfaction with one's life and overall fulfilment, while helping to protect against depression, anxiety, stress, emotional problems and negative emotions, particularly among children exhibiting symptoms of psychological disorders [22,23]. Studies analyzing mindfulness interventions have shown that such program can have beneficial effects for children, particularly by helping them to overcome emotional problems and negative emotions, and by boosting social and emotional skills, wellbeing and self-esteem, particularly in children with emotional problems or stress issues [22,25]. Yoga, regarded as encompassing aspects of mindfulness and meditation as well as physical postures, breathing and relaxation techniques, may also have positive effects in terms of reducing anxiety, depression and inhibition, while encouraging feelings of physical and psychological wellbeing, self-esteem, resilience, attention and even educational performance [26].…”
Section: Organization and Structure Of Educational Activitiesmentioning
confidence: 99%
“…A holistic approach to mental health in schools considers the whole person, addressing not only cognitive development, but also emotional, social, and psychological wellbeing [27]. This approach fosters the growth of well-rounded individuals who are better prepared for life beyond school.…”
Section: Prioritization Of Mental Health In Schoolsmentioning
confidence: 99%